Video-EEG in Diagnosis of Epilepsy in Retarded Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Video-EEG monitoring was used to distinguish epileptic and non-epileptic events in 193 children, mean age 9.6 years, who presented with paroxysmal symptoms of uncertain etiology at Children's Hospital, Los Angeles, CA.